Managing the Modern Law Firm - Empson, Laura (Ascent Audio, 2019)
The last ten years have been a period of extraordinary change for law firms. The rapid growth of corporate law firms and the emergence of global mega-firms have strained the traditional partnership model of management. Some managers of law firms are appalled at the creeping "corporatism" that they fear may result. However, a growing number believe that it is time to move on and adopt more contemporary forms of structure and management. In Managing the Modern Law Firm scholars and legal practitioners examine the latest insights from management research, to enable law firms successfully to meet the challenges of this new business environment.